Social revitalisation of urban regions - Peter M.J. Pol; Leo Van den Berg; Jan van der Meer (European Regional Science Association (ERSA), 2001)
This paper aims to analyse how social revitalisation can contribute to an (economically) attractive urban region and how such policies can be made more effective and efficient. To stimulate re-urbanisation and attract new economic activities and residents, much attention is paid to the concept of ''the attractive city''. Cities are observed to switch their focus from hardware (tangible services) to software (image, quality of life) and orgware (organising capacity). To enhance the effectiveness of social policy is in that context often considered a spearhead for cities. In practice, social policy does not always seem to be carried out effectively. Much money may be spent on solving a problem without effective progress being accomplished. Moreover, the results of social policy are often hard to measure, so that a lack of purpose may not be easy to detect. The paper is based on a comparative research of eight European urban regions.
Keywords: 330